PEMODELAN SISTEM FOC KENDALI KECEPATAN MOTOR INDUKSI 3 FASA MENGGUNAKAN PI CONTROLLER - Sri Muntiah Andriami; Era Purwanto; Hary Oktavianto; Kadek Reda Setiawan Suda; Abdullah Aziz Muntashir (Jurnal Pendidikan Teknologi dan Kejuruan, 2023)
The speed regulation on this 3-phase induction motor uses a PI Controller by applying the Field Oriented Control (FOC) method, one part of the vector control method. One of the systems developed in this study is the speed control of a 3-phase induction motor by modeling the Field Oriented Control (FOC) system with a speed controller using a PI Controller, the results obtained from speed regulation are that to achieve steady state it only takes 1 to 2 seconds with Stedy error average is 1.175% with not too big rise time and overshoot. By modeling the FOC system using the PI Controller, it is able to overcome the weakness in the speed of the induction motor and provide high control system performance criteria, by suppressing the overshoot and steady state error to close to zero, and the rise time and settling time are relatively fast compared to the open loop controller.